Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve this problem, we need to use the concept of direct variation. When we say that [tex]\(y\)[/tex] varies directly as [tex]\(x\)[/tex], we mean that there is a constant [tex]\(k\)[/tex] such that:
[tex]\[ y = kx \][/tex]
Given the information, [tex]\( y = 48 \)[/tex] when [tex]\( x = 6 \)[/tex]. We can use this to find the constant [tex]\(k\)[/tex]:
[tex]\[ 48 = k \cdot 6 \implies k = \frac{48}{6} \][/tex]
Now, we need to find the value of [tex]\(y\)[/tex] when [tex]\( x = 23 \)[/tex]. We use the expression of direct variation again, substituting [tex]\(k\)[/tex] and [tex]\( x = 23 \)[/tex] into our equation:
[tex]\[ y = k \cdot 23 \][/tex]
Since we already determined that [tex]\( k = \frac{48}{6} \)[/tex], we can substitute this into the equation:
[tex]\[ y = \left( \frac{48}{6} \right) \cdot 23 \][/tex]
Thus, the expression that shows how to find [tex]\( y \)[/tex] when [tex]\( x = 23 \)[/tex] is:
[tex]\[ y = \frac{48}{6} \cdot 23 \][/tex]
From the options given, the closest form of this expression is:
[tex]\[ y = \frac{48}{6}(2) \][/tex]
However, be cautious with the options given because there seems to be a discrepancy in variables and choice logic. The correct theoretical framework is shown above, yet none of the options perfectly outline the situation for [tex]\( x = 23 \)[/tex] due to a potential misprint in the answer options.
[tex]\[ y = kx \][/tex]
Given the information, [tex]\( y = 48 \)[/tex] when [tex]\( x = 6 \)[/tex]. We can use this to find the constant [tex]\(k\)[/tex]:
[tex]\[ 48 = k \cdot 6 \implies k = \frac{48}{6} \][/tex]
Now, we need to find the value of [tex]\(y\)[/tex] when [tex]\( x = 23 \)[/tex]. We use the expression of direct variation again, substituting [tex]\(k\)[/tex] and [tex]\( x = 23 \)[/tex] into our equation:
[tex]\[ y = k \cdot 23 \][/tex]
Since we already determined that [tex]\( k = \frac{48}{6} \)[/tex], we can substitute this into the equation:
[tex]\[ y = \left( \frac{48}{6} \right) \cdot 23 \][/tex]
Thus, the expression that shows how to find [tex]\( y \)[/tex] when [tex]\( x = 23 \)[/tex] is:
[tex]\[ y = \frac{48}{6} \cdot 23 \][/tex]
From the options given, the closest form of this expression is:
[tex]\[ y = \frac{48}{6}(2) \][/tex]
However, be cautious with the options given because there seems to be a discrepancy in variables and choice logic. The correct theoretical framework is shown above, yet none of the options perfectly outline the situation for [tex]\( x = 23 \)[/tex] due to a potential misprint in the answer options.
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.